ASPEK SOSIAL DALAM IMPLEMENTASI SISTEM INFORMASI DI PERPUSTAKAAN - Ida Widiastuti (Jurnal Kajian Informasi dan Perpustakaan, 2013)
This research was using Social Construction Of Technology (SCOT Theory) and Technological Frame Theory with  Qualitative Methodelogy, which is purposed to make complete delineation about social cognitive aspect in the  implementation of information system technology at Jember University Library. To get the purposed, we used interviews and observation.  The interviews was taking the following structure based on Technological Frames Theory and its concept of nature of technology; technology strategy; technology in use. According to framework of Orlikowski and Gash (1994), the actors in this research are professional groups which is categorized as managers; technologists; and users. The result are shown that in the implementation of information technology at Jember University Library, beside similarity, also found a lot of dissimilarity on shared cognitive among social groups.  Dissimilarity mean the actor  are  in the incongruent position. According   to Technological  Frames theory, if incongruent found, organizations will have difficulities and concflicts in developing, implementing and using technologies.Penelitian ini menggunakan Konstruksi Sosial Teknologi (SCOT Teori) dan Frame Teori Technological dengan metode kualitatif, yang bertujuan untuk membuat tentang aspek sosial kognitif dalam pelaksanaan sistem teknologi informasi di Perpustakaan Universitas Jember. Penelitian ini, menggunakan wawancara dan observasi. Wawancara mengambil struktur berdasarkan teknologi Frames Teori dan konsep dari sifat teknologi; strategi teknologi; teknologi yang digunakan. Menurut kerangka Orlikowski dan Gash (1994), aktor dalam penelitian ini adalah kelompok profesional yang dikategorikan sebagai manajer; teknologi; dan pengguna. Hasilnya ditunjukkan bahwa dalam implementasi teknologi informasi di Jember Perpustakaan Universitas, di samping kesamaan, juga menemukan banyak perbedaan di shared kognitif antara kelompok-kelompok sosial. Perbedaan berarti aktor berada dalam posisi kongruen. Menurut teori teknologi Frames, jika kongruen ditemukan, organisasi akan memiliki difficulities dan concflicts dalam mengembangkan, menerapkan dan menggunakan teknologi.